Achieving low activation energy and double-peak texture after hot deformation of Mg–Al–Zn–Ca–Mn–Zr alloy and enabling the strength and ductility - Abdul Malik; Jianyu Long; Chaun Li (Journal of Materials Research and Technology, 2023)
In this study, the hot-deformation behavior of a die-casted Mg–Al–Zn–Ca–Mn–Zr alloy was investigated in the temperature range of 548–673 K and the strain rate range of 0.0001–1 s−1. The constitutive equation and processing maps were also developed to describe the flow stress behavior. The numerical simulation result revealed an average activation energy of ∼139.4 kJ mol−1, which is lower than the previously reported AZ31 Mg alloys. Subsequently, the low activation energy imparted a high degree of dynamic recrystallization and was mainly attributed to alloying elements Ca, Mn, and Zr. For optimum hot working parameters, processing maps displayed two different domains, the temperature range of 573–673 K for a strain rate range of 0.001–0.01 s−1 with a peak efficiency of 33% and a temperature of 673 K at a high strain rate of 0.01 s−1 with a peak efficiency of 31%. The microstructure evolution confirmed the validity of parameters and revealed high dynamic recrystallization. The average grain size ∼21.1 μm, ∼15.4 μm, and ∼16.1 μm were achieved at temperatures of 573 K, 623 K, and 673 K under a strain rate of 0.001 s−1. The profuse grain refinement is attributed to the pronounced accumulation of dislocation on grain boundaries and on the eutectic phases. In addition, the morphology of the eutectic phases was broken with the increase in the strain rate and temperature. Thus, the α-Mg and eutectic phases bear the compressive stresses and promote the dynamic recrystallization activity. Last but not least, the double peak texture after hot deformation was developed, which is one of the engineers' main requirements for enhancing the Mg alloy's ductility. Based on the above discussion, the hot deformed specimens exhibited an ultimate compressive strength of ∼340 MPa and elongated to fracture >25%. Consequently, this study enables the understanding of the broad use of Mg–Zn–Al–Ca–Mn–Zr alloys for automobile applications.